Migrant Labor Remittances in the South Asia Region - World Bank (Washington, DC, 2012)
Bangladesh, India, Pakistan and Sri Lanka have all experienced a sharp increase in remittances during the past decade, and are the countries among the top 20 receivers of remittances. The report provides a strategic overview of key issues relating to the remittances industry in the South Asia region, and, builds on recent Bank research on the subject, that prominently features this region. This study basically focuses on the region's distinguishing characteristics: large migrant population of semi-skilled, and unskilled workers (largely concentrated in the Arabian Gulf countries) contributing to rising remittance flows; the presence of dedicated public institutions, and government financial incentives aimed at facilitating, and providing support for temporary migration, and remittance inflows; The existence of state bank networks, with immense potential for an effective remittance financial market; and, The widespread use of trade-related informal remittance channels by both legal, and illegal migrants. The increase in remittance volumes, has renewed academic, and public policy interest in their potential to reduce poverty, and economic vulnerability, improve family welfare, and stimulate local economic development, in the face of lower foreign direct investment (FDI) flows. The study analyzes the impact of international remittances on poverty, using a growth-poverty model, which assumes that economic growth - as measured by increases in mean per capita income - will reduce poverty. It finds that, when estimated values for unofficial remittances are added to official remittance figures, total remittances reduce the level of poverty in south Asia. Recommendations to maximize the network's full potential suggest among others: shared payments systems platforms; public-private partnerships across infrastructure, products, and services are necessary for countries in the region that seek the types of gains attained elsewhere; cross selling, i.e., it is essential that as the profitability of the conventional remittance business model continues to decline, formal financial institutions invest in cross-selling complimentary financial services, and products.